AMPA Receptors in the Therapeutic Management of Depression - Bleakman, D.; Alt, A.; Witkin, J. M. (CNS & Neurological Disorders - Drug Targets, 2007)
There is an increasing body of evidence implicating a role for α-amino-3-hydroxy-5-methyl-4 isoxazoleproprionic acid (AMPA) receptors in major depression and in the actions of antidepressant drugs. Alterations in AMPA receptors and other ionotropic glutamate receptors have been reported in depression, and following antidepressant treatment. Compounds which augment signaling through AMPA receptors (AMPA receptor potentiators) exhibit antidepressant-like behavioral effects in animal models, and produce neuronal effects similar to those produced by currently available antidepressants, including neurotrophin induction and increases in hippocampal progenitor cell proliferation. Additionally, the antidepressant fluoxetine has been found to alter AMPA receptor phosphorylation in a manner that is expected to increase AMPA receptor signaling. Data from mutant mice suggest that AMPA receptors may regulate the expression of brainderived neurotrophic factor, a neurotrophin which has been implicated in the actions of antidepressant therapies. Combined, these data suggest that AMPA receptors may be in a key position to regulate mood disorders, and that compounds which target AMPA receptors may prove useful in the clinical management of depression.
Keywords: NMDA receptor